VeggieTales. 'Twas the night before Easter [videorecording (DVD)] - Nawrocki, Michael; Vischer, Phil (Big Idea's VeggieTales., 2011)
Marlee tries to save the local town theater at Easter time, but is worried the attention will be shining on singing sensation Cassie Cassava, set to perform in her hometown church's Easter service, instead of the musical she is putting on for the town.